Effects of re-warm-up protocols on the physical performance of soccer players: A systematic review with meta-analysis - González Fernández, Francisco; Sarmento, Hugo; Infantes-Paniagua, Álvaro; Ramirez-Campillo, Rodrigo; González-Víllora, Sixto; Clemente, Filipe (Biology of Sport, 2023)
This systematic review aimed to (1) identify and summarize studies that have examined the effects of re-warm-up (RWU) protocols on the physical performance of soccer players (vertical jump height and sprint time) and (2) establish a meta-comparison between performing a re-warm-up and not performing one regarding the outcomes of the aforementioned outcomes. A systematic review of EBSCO, PubMed, SciELO, SPORTDiscus, and Web of Science databases was performed on 12 January, 2021, according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. From the 892 studies initially identified, four studies were reviewed, and three of these were included in the present meta-analysis. Compared to a control condition, there was a moderate effect of RWU on vertical jump height (ES = 0.66; p = 0.001; I2 = 0.0%). However, compared to a control condition, there was a trivial effect of RWU on linear sprint time (ES = 0.19; p = 0.440; I2 = 38.4%). The nature of RWU enhances the performance of players with an emphasis on actions requiring vertical jumps. Therefore, the results provide essential information that soccer coaching staff can use to improve the performance of their teams. The limited number of studies available for the meta-analysis may have magnified the impact of heterogeneity on linear sprint time findings. More high-quality studies, with homogeneous study designs, may help to clarify the potential benefits of RWU for linear sprint time.